Biodiesel Synthesis of Crude Palm Oil By Using Bifunctional Catalyst Sn/Kaolinite and K2CO3 - Abdullah Yamani Noor; Thamrin Usman; Nelly Wahyuni (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
The relatively high content of free fatty acids in crude palm oil inhibits the direct synthesis of biodiesel. The use of a bifunctional solid heterogeneous catalyst allows for simultaneous transesterification-esterification reactions and facilitates the purification of the final product from the reaction mixture. This study aimed to synthesize biodiesel from crude palm oil via the use of a Sn-K/metakaolinite catalyst in a simultaneous transesterification-esterification reaction. Biodiesel synthesis was carried out using crude palm oil before and after pretreatment. The optimum conditions were determined by the reaction time (1–5 hours), reactant molar ratio (1:2, 1:4, 1:6, 1:8, 1:10, 1:12), and catalyst concentration (1,3, 5,7 and 9%), and the resulting methyl esters were measured for density, viscosity, and free fatty acids and analyzed via GC‒MS. The results obtained indicate that biodiesel synthesis was successfully carried out with completely converted methyl esters via treated crude palm oil. The optimum conditions for the reaction included a reaction time of 3 hours, a catalyst concentration of 5% and a reactant molar ratio of 1:10. The resulting methyl ester product has a density of 0.86 g/mL, a viscosity of 3.02 cSt and a free fatty acid content of 0.059%. The results of the GC‒MS analysis revealed that the dominant methyl ester components were methyl oleate and methyl palmitate. The synthesis of biodiesel from crude palm oil with a Sn-K/metakaolinite catalyst has been proven to be carried out in simultaneous transesterification-esterification reactions with good catalytic activity.